Establishment of Patient-Derived Organoids and Drug Screening for Biliary Tract Carcinoma - Saito, Yoshimasa; Muramatsu, Toshihide; Kanai, Yae; Ojima, Hidenori; Sukeda, Aoi; Hiraoka, Nobuyoshi; Arai, Eri; Sugiyama, Yuko; Matsuzaki, Juntaro; Uchida, Ryoei; Yoshikawa, Nao; Furukawa, Ryo; et al. (Cell reports (Cambridge), 2019)
Biliary tract carcinomas (BTCs) are among the most aggressive malignancies and have a poor prognosis. Here, we successfully established organoid lines derived from intrahepatic cholangiocarcinoma, gallbladder cancer, and neuroendocrine carcinoma of the ampulla of Vater. These organoids derived from BTCs were cultured stably for >1 year and closely recapitulated the histopathology, gene expression, and genetic alterations evident in the primary tumors. Gene expression profiling of the organoids revealed that SOX2 could be a potential prognostic biomarker for patients with BTC. We screened a compound library consisting of drugs used clinically for their ability to suppress organoids derived from BTCs and found that the antifungal drugs amorolfine and fenticonazole significantly suppressed the growth of organoids derived from BTCs with minimal toxicity to normal biliary epithelial cells. Patient-derived organoids may be a powerful research tool for the clarification of molecular pathogenesis and the discovery of biomarkers and therapeutic drugs for refractory cancers. [Display omitted] •Establishment of organoids derived from biliary tract carcinoma (BTC) patients•Biological similarity between the primary BTC tissues and established organoids•Identification of SOX2, KLK6, and CPB2 as prognostic biomarkers for BTC patients•Drug screening identified antifungal drugs as potential therapeutic agents for BTC Saito et al. were successful in establishing and long-term in vitro culturing of organoids derived from patients with intrahepatic cholangiocarcinoma, gallbladder cancer, and neuroendocrine carcinoma of the ampulla of Vater. Patient-derived organoids can be a powerful preclinical model to identify prognostic biomarkers and therapeutic agents for biliary tract carcinoma.